AI4SE and SE4AI: Setting the Roadmap toward Human‐Machine Co‐Learning. Issue 4 (9th February 2023) - Pepe, Kara; Hutchison, Nicole
ABSTRACT: Artificial intelligence (AI) and machine learning (ML) technology are becoming increasingly critical in systems: both to provide new capabilities and in the practice of systems engineering itself, especially as digital transformation improves the automation of many routine engineering tasks. The application of AI, ML, and autonomy to complex and critical systems encourage the development of new systems engineering methods, processes, and tools. This article highlights a series of workshops conducted jointly by the US Army Combat Capabilities Development Command Armaments Center (CCDC AC) Systems Engineering Directorate and the Systems Engineering Research Center (SERC). These workshops focus on the relationships between AI and systems engineering and elicit input from hundreds of stakeholders across government, industry, and academia. They also provide critical direction to the SERC's research roadmap on AI/autonomy as it looks towards the long‐term outcome of "human‐machine co‐learning." Though the workshops are US‐centric, the lessons and insights gained are applicable globally.